2015
DOI: 10.1016/j.egypro.2015.03.097
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance Testing Procedure for Linear Fresnel Reflector Solar Systems in Utility-Scale Solar Thermal Power Plants

Abstract: This paper presents a methodology for performance acceptance testing of solar boilers using Linear Fresnel Reflectors (LFR) with Direct Steam Generation (DSG). The proposed methodology is based on relevant ISO and American standards applying an adapted parameter identification technique. Discussions regarding measurement requirements and uncertainty analysis are also provided. This methodology will be eventually consolidated thanks to real operational data on next LFR power plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…The IAM for Fresnel reflectors is a function of both longitudinal and transverse angles (see Figure 3 to identify both angles), i.e., IAM = IAM(θ l , θ t ). It is usual to define the incidence angle modifier as the product of the longitudinal modifier K l and the transverse modifier K t so that it is possible to obtain both parameters independently [14,33].…”
Section: Resultsmentioning
confidence: 99%
“…The IAM for Fresnel reflectors is a function of both longitudinal and transverse angles (see Figure 3 to identify both angles), i.e., IAM = IAM(θ l , θ t ). It is usual to define the incidence angle modifier as the product of the longitudinal modifier K l and the transverse modifier K t so that it is possible to obtain both parameters independently [14,33].…”
Section: Resultsmentioning
confidence: 99%
“…The performance model used and pass/fail criteria for the acceptance test are a contractual matter approved by the involved parties. Yang et al [32] reported that the test procedure guidelines provided by NREL [5, 7] and [30, 31] concerning PT and SPT systems are broadly applied because ASME PTC 52 is currently under review by ASME committee [32].…”
Section: Introductionmentioning
confidence: 99%
“…Οι εργασίες κυρίως στηρίζονται στη χρήση του διακριτοποιημένου συντελεστή γωνίας πρόσπτωσης και στο συνδυασμό οπτικών μοντέλων και μετρήσεων. Οι Yang et al [72] παρουσίασαν μία μεθοδολογία για την αξιολόγηση της απόδοσης των ηλιακών συλλεκτών Fresnel με απευθείας ατμοπαραγωγή. Οι Hofer et al [73] παρουσίασαν τα αποτελέσματα αξιολόγησης των μετρήσεων και χαρακτηρισμού ενός μικρής κλίμακας συλλέκτη Fresnel μέσω δύο μεθόδων ανάλυσης (dynamic και quasi-dynamic).…”
Section: σχήμα 2-8 : θέσεις πρωτεύοντων ανακλαστήρωνunclassified